2018 13th Iberian Conference on Information Systems and Technologies (CISTI) 2018
DOI: 10.23919/cisti.2018.8399288
|View full text |Cite
|
Sign up to set email alerts
|

The potential of cooperative networks to leverage tourism in rural regions

Abstract: -Rural tourism can be an opportunity to perform the development of the most disadvantaged rural areas. In this pursuit, there are many challenges to face for make this sector competitive and economically viable. This paper focuses on develop a better understanding of rural tourism and the need for cooperative paradigms that can leverage its competitiveness. In this context, a conceptual model and a technology-based system is presented to bridge the gap between heritage resources and business opportunities to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…Cooperation, especially between providers from different stages of the value chain, have long been considered the most important success factor in cultural tourism (Fo ¨hl and Pro ¨bstle, 2013;Steinecke, 2013;Hausmann, 2019;Du Cros and McKercher, 2020). Especially in rural areaswith a typically small-scale provider structure and, as a result, a poorly integrated offer and a low responsiveness to tourists' demandsstakeholders rely on entering into such long-term and competitive cooperation (Drda-Ku ¨hn and Wiegand, 2010; Polo and Frias, 2010;Neumeier and Pollermann, 2014;Mendonca et al, 2018). The study by Burzinski et al (2018) also draws attention to the challenges of cultural tourism in rural areas.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cooperation, especially between providers from different stages of the value chain, have long been considered the most important success factor in cultural tourism (Fo ¨hl and Pro ¨bstle, 2013;Steinecke, 2013;Hausmann, 2019;Du Cros and McKercher, 2020). Especially in rural areaswith a typically small-scale provider structure and, as a result, a poorly integrated offer and a low responsiveness to tourists' demandsstakeholders rely on entering into such long-term and competitive cooperation (Drda-Ku ¨hn and Wiegand, 2010; Polo and Frias, 2010;Neumeier and Pollermann, 2014;Mendonca et al, 2018). The study by Burzinski et al (2018) also draws attention to the challenges of cultural tourism in rural areas.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…However, what has not been studied so far are the pitfalls for cooperation projects that occur especially in cultural tourism marketing in rural areas. In contrast, various studies have already concluded that such cooperation is particularly useful in the context of implementing digital applications (Buhalis and Amaranggana, 2015;Mendonca et al, 2018;Abidin et al, 2019). But one of the weaknesses of these studies is, that the thematic focus has so far either remained too general in terms of the role or advantages of digital applications for the development of cooperation (Del Chiappa and Baggio, 2015;Mendonca et al, 2018) or that the studies focus on the exchange of data and information (Buhalis and Amaranggana, 2015;Buhalis and Leung, 2018;Abidin et al, 2019).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 3 more Smart Citations